Investigations of Sol-Gel ZnO Films Nanostructured by Reactive Ion Beam Etching for Broadband Anti-Reflection. (14th September 2017) - Visser, D.; Ye, Z.; Prajapati, C. S.; Bhat, N.; Anand, S.
Abstract : A novel ZnO dry etching approach is introduced using reactive ion beam etching of thick sol-gel ZnO layers for controlled nanodisk/nanocone array fabrication. In this approach the same system can be used for the colloidal lithography mask (silica particles) size reduction by a fluorine-based chemistry and etching of the ZnO nanostructures by a CH4 /H2 /Ar chemistry. This resulted in a ZnO:SiO2 etch selectivity of ∼3.4 and etch rate of ∼56 nm/min. Thick sol-gel ZnO layers, nanodisk arrays and (truncated) nanocone arrays were fabricated and their optical properties analyzed by finite-difference time-domain simulations and spectrally-resolved total/specular reflectivity measurements. The demonstrated broadband omnidirectional anti-reflection, controlled nanostructure period/geometry and low absorption in the visible-NIR spectrum makes these sol-gel ZnO nanostructures very interesting for many optoelectronic applications, including photovoltaics.